Application of Tiab's Direct Synthesis technique to transient pressure response of non-Newtonian fluids in vertical wells - Meindl, Irina Desiree Katime (My University, 2000)
Non-Newtonian fluids are very common during drilling, fracture operations and enhanced oil recovery processes. When a reservoir contains a non-Newtonian fluid such as those injected during polymer flood or the production of heavy oil, well test data cannot be interpreted using Newtonian fluid flow models. The resulting analysis would be erroneous because non-Newtonian fluids behave rather differently. These results suggest the need for a thorough study of the behavior of non-Newtonian fluids in the reservoir and also a new look at the flow of those fluids in porous media. This study presents an interpretation technique for pressure behavior of non-Newtonian fluid flow in a homogeneous reservoir without type-curve Matching. The inclusion of a no-flow and/or a constant pressure line is also investigated. First, the TSD (Tiab's Direct Synthesis) technique was applied for analyzing the pressure behavior of a well located in (1) an infinite reservoir and, (2) near a linear boundary where wellbore storage and skin effects were considered. The analysis required the generation of type-curve sets for different wellbore storage and skin values. A step-by-step procedure is presented for the calculation of the reservoir parameters: the permeability/viscosity ratio, wellbore storage coefficient, skin factor and the distance to the nearest boundary without the use of type-curve Matching. The procedure is illustrated by a numerical example.
Keywords: Non-Newtonian fluids; Oil field flooding; Hydrocarbon reservoirs; Oil wells